Pengaruh Presentase Bungkil Kedelai yang Terfermentasi dalam Pakan Buatan terhadap Pertumbuhan Post Larva Udang Vannamei (Litopenaeus Vannamei) - Mizan Affan; Sutaman Sutaman; Ninik Umi Hartanti (Manfish: Jurnal Ilmiah Perikanan dan Peternakan, 2026)
Vaname shrimp (Litopenaeus vannamei) has a fast growth rate, good tolerance to a wide range of salinity and temperature, and resistance to several common shrimp diseases. Vaname shrimp has an efficient feed conversion making it more economical to cultivate, and its international market demand is high. The research method used four treatments of fermented soybean meal doses, namely 0% (control), 15%, 25%, and 35%, each with 3 replications. The feed was formulated using Pearson’s Square method targeting 35% protein, and the soybean meal was fermented using tempe yeast method. The observed parameters included daily growth rate (%), absolute weight gain (grams), survival rate (%), feed utilization efficiency (FUE), and feed conversion ratio (FCR). The results showed that the treatment with 25% fermented soybean meal dose gave the best results with a daily growth rate of 6.42%, absolute weight gain of 0.22 grams, survival rate of 90.66%, and the highest feed utilization efficiency of 0.66.